2022
DOI: 10.1002/ppp3.10314
|View full text |Cite
|
Sign up to set email alerts
|

Scientists' warning to humanity on tree extinctions

Abstract: Societal Impact StatementTrees play vital roles in many of the world's ecosystems while providing many benefits to people. New evidence indicates that a third of tree species are threatened with extinction, representing a tree extinction crisis. Here we demonstrate how tree species extinction will lead to the loss of many other plants and animals and significantly alter the world's ecosystems. We also show how tree extinction will negatively affect billions of people through loss of livelihoods and benefits. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(32 citation statements)
references
References 110 publications
0
32
0
Order By: Relevance
“…With 142,577 species assessed in April 2022, this goal was not met. Nonetheless, in the current UN Decade of Ecosystem Restoration, with the aim to prevent, halt and reverse the degradation of ecosystems on every continent and in every ocean (Farrell et al, 2021), it remains important to include more species on the IUCN Red List as a first step to more equal conservation effort (Rivers et al, in press). A major reason for this imbalance in the IUCN Red List is that often data for Red List assessments are lacking for lesser‐known species.…”
Section: Introductionmentioning
confidence: 99%
“…With 142,577 species assessed in April 2022, this goal was not met. Nonetheless, in the current UN Decade of Ecosystem Restoration, with the aim to prevent, halt and reverse the degradation of ecosystems on every continent and in every ocean (Farrell et al, 2021), it remains important to include more species on the IUCN Red List as a first step to more equal conservation effort (Rivers et al, in press). A major reason for this imbalance in the IUCN Red List is that often data for Red List assessments are lacking for lesser‐known species.…”
Section: Introductionmentioning
confidence: 99%
“…Because all species have distinct ranges of conditions that determine where they can occur (Wiens, 2016), the impact of these changes for species (including humans) cannot be denied (Pecl et al, 2017; Román‐Palacios & Wiens, 2020), although the exact traits that determine species ranges are still not clear (Freeman et al, 2018; MacLean & Beissinger, 2017). Understanding how different taxa are affected by these changes is key in order to inform measures for conservation and protection (Rivers et al, 2022), something especially important in this UN Decade on Ecosystem Restoration. Given that approximately 60% of all vascular plant species occur in tropical forests (Burley, 2002; FAO & UNEP, 2020), understanding the impact of ecosystem changes in this biome is crucial.…”
Section: Introductionmentioning
confidence: 99%
“…Covering approximately 7% of the terrestrial portion of the earth's surface (Hill & Hill, 2001), tropical rain forests harbour approximately 45% of all terrestrial species (Eiserhardt et al, 2017), which includes approximately three fourth of all tree species (Singh & Sharma, 2009). This is equivalent to an estimated 40,000-53,000 tropical tree species (Rivers et al, 2022;Slik et al, 2015) out of a total between 60,000-73,000 estimated worldwide (Beech et al, 2017;Botanic Gardens Conservation International, 2021;Cazzolla Gatti et al, 2022). The tropical rain forest is distributed across sub-Saharan Africa, Madagascar, South-East Asia, northern Australia, a large portion of the islands of the Pacific Ring of Fire and Central and South America (Eiserhardt et al, 2017;Morley, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Trees play major functional roles in the world’s ecosystems where they protect biodiversity and are important carbon sequesters that mitigate climate change (1; 2) . They also provide a wide range of socioeconomic benefits to billions of people (3) that include being important sources of nutrient-rich foods that support healthy diets (4; 5) . By growing diverse food trees in their agroforestry systems, for example, smallholder farmers can achieve year-round nutritional security, while the sale of these foods supports broader healthful consumption (6) .…”
Section: Introductionmentioning
confidence: 99%
“…Developed primarily by combining data from GlobalTreeSearch with the World Checklist of Useful Plant Species, GlobUNT includes 14,014 tree species that can be filtered for ten major use categories, across 242 countries and territories. In a subcontinental comparison GlobUNT revealed that Malesia had the highest useful tree species richness (3,349) and was also richest for materials (2,723), medicines (1,533), human food (958), fuel (734), environmental uses (632), social uses (614), animal food (443), poisons (322) and invertebrate food (266).…”
mentioning
confidence: 99%